The role of language policy in social developing of Kazakhstan (Journal of Philosophy Culture and Political Science, 2019)
This article discusses some of the problems of language policy in Kazakhstan and the role of language relations in social development. Conceptual convergence of language policy and social development requires a strategic view of the role and importance of language policy in development of a national community. Impact of language policy on social development is determined by the extent to which it contributes to lower or raise the level of intellectual and volitional capacity of the population in comparison with other countries, the extent to which it destroys the immune system and enhances cultural citizens, making 'them susceptible or immune to the information-psychological effects, etc. Keywords: social developing, language policy, Kazakhstan, message.